Salvia officinalis L. induces alveolar bud growing in adult female rat mammary glands - Monsefi, Malihezaman (Avicenna J Phytomed, 2015)
OBJECTIVES: In traditional medicine Salvia officinalis (sage) has been used as menstrual cycle regulator. In the present study the effects of sage extract on breast tissue were examined. MATERIALS AND METHODS: Fourteen female rats were divided into two groups: 1) Distilled water-treated rats (Con) that were gavaged with 1ml distilled water and 2) Saliva officinalis hydroalcoholic extract (SHE)-treated rats that were gavaged with 30mg/kg/body weight of sage extract for 30 days. The estrus cycle changes were monitored by daily examination of vaginal smear. Whole mounts of right pelvic breast were spread on the slide and stained by carmine. The number of alveolar buds (ABs) type 1 and 2 and lobules of mammary gland were scored. Tissue sections of left pelvic mammary gland were prepared and its histomorphometrical changes were measured. Blood samples were taken from dorsal aorta and estradiol and progesterone concentrations were measured using radioimmunoassay. RESULTS: Estrous cycles decreased significantly in SHE-treated animals. The number of alveolar buds and lobules in mammary gland whole mount of SHE-treated group were higher than the Con group. The number and diameter of ducts in histological section of mammary gland in SHE-treated group increased as compared to the Con group. CONCLUSION: Sage promotes alveologenesis of mammary glands and it can be used as a lactiferous herb.